Reconstituting Microtubules: A Decades-Long Effort From Building Block Identification to the Generation of Recombinant α/β-Tubulin - Ti, Shih-Chieh (Frontiers in Cell and Developmental Biology, 2022)
Microtubules are cytoskeletal filaments underlying the morphology and functions of all eukaryotic cells. In higher eukaryotes, the basic building blocks of these non-covalent polymers, ɑ- and β-tubulins, are encoded by expanded tubulin family genes (i.e., isotypes) at distinct loci in the genome. While ɑ/β-tubulin heterodimers have been isolated and examined for more than 50 years, how tubulin isotypes contribute to the microtubule organization and functions that support diverse cellular architectures remains a fundamental question. To address this knowledge gap, in vitro reconstitution of microtubules with purified ɑ/β-tubulin proteins has been employed for biochemical and biophysical characterization. These in vitro assays have provided mechanistic insights into the regulation of microtubule dynamics, stability, and interactions with other associated proteins. Here we survey the evolving strategies of generating purified ɑ/β-tubulin heterodimers and highlight the advances in tubulin protein biochemistry that shed light on the roles of tubulin isotypes in determining microtubule structures and properties.